SISTENSI Mg-A1-DIKLOFENAK HYDROTALCITE MELALUI REAKSI PENUKARAN ION - , Astuti ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Mg-Al-diclofenac hydrotalcite has been synthesized via ion exchange reaction. The research was initiated with synthesizing Mg-Al-NO3 and Mg-Al-Cl hydrotalcites followed by performing the ion exchange with diclofenac ion. Ion exchange capacity and its kinetics parameters were observed based on the cation mole ratio. The characterization of hydrotalcite before and after the ion exchange as well as after regeneration was conducted using XRD, FTIR and AAS. The results showed that the chloride and nitrate ions on the interlayer of Mg/Al hydrotalcite can be exchanged with diclofenac ion with giving exchange capacities of 117 and 88 meq diclofenac/100 g hydrotalcite, respectively. The ion exchange reactions obeyed the first order reaction with the reaction rate constant of 0,0018 s-1 and 0,0052 s-1, respectively. The FTIR and XRD analyses showed that Mg/Al- diclofenac could be regenerated with nitrate and chloride anions, where the ion exchange capacity of Mg-Al-NO3 hydrotalcite was higher than that of Mg-Al-Cl hydrotalcite.